Careers for Students with Special Educational Needs Perspectives on Development and Transitions from the Asia-Pacific Region - Yuen, Mantak; Beamish, Wendi; Solberg, V. Scott H.; SpringerLink (Online service) (Singapore : Springer Singapore : Imprint: Springer, 2020)
This book addresses in detail a range of issues in connection with preparing individuals with disabilities or other special needs for gaining employment and planning a career path beyond school. It presents strategies for personnel preparation, parent education, effective programs for career development and transitions, policies and policy research, and useful tools for assessment and intervention. The clear explanations of essential theories, research findings, policies, and practices for career development ensure that readers gain a deeper understanding of all the issues involved. Most importantly, they will learn several strategies that can be used to prepare students for employment within global and Asia-Pacific regional contexts.
Part 1. Issues in Career Development and Transitions -- Chapter 1. Career Development Policy Strategies for Supporting Transition of Students with Special Educational Needs and Disabilities -- Chapter 2. Career Development of Students with Intellectual Disability: A Systems Theory Perspective -- Chapter 3. Considering the Fourth Industrial Revolution in the Preparation of Learners with and Without Disabilities -- Chapter 4. Webs of Supportive Relationships: A Positive Youth Development Approach to Career and Workforce Development with Risk-Immersed Youth -- Chapter 5. Career Development of Twice-Exceptional Individuals: Present and Future Issues -- Part 2. Strategies for Personnel Preparation, Parent Education and Disability-Specific Issues -- Chapter 6. Strategies to Promote Effective Secondary Special Education and Transition Content into Teacher Preparation Coursework -- Chapter 7. Strategies to Promote Effective Secondary Special Education and Transition Content into Teacher Preparation Coursework -- Chapter 8. Social Workers$1 (BStrategies for Supporting Career Transition for Disadvantaged Girls with SEN: A Hong Kong Case Study of Class in Digital Drawing -- Chapter 9. The Power of Parent Education: Transition Planning for Students with Moderate to Severe Disabilities -- Part 3. Effective Policies, Programs and Approaches for Career Development and Transitions in the Asia-Pacific Region -- Chapter 10. Creating New Narratives to Give Hope and Optimism to At-risk Students in Singapore: A Case for Vocational Guidance and Career Counselling Intervention -- Chapter 11. Views of Parents on a Career and Life Planning Program for Junior Secondary Students with Special Educational Needs: A Qualitative Study in Hong Kong -- Chapter 12. Career Guidance for Gifted Students in Hong Kong -- Chapter 13. Career Guidance for High School Students with Specific Learning Difficulties: A Hong Kong Perspective -- Chapter 14. Career Guidance for Students with Special Educational Needs in New Zealand -- Chapter 15. Improving Transition-Focused Education for Students with Special Educational Needs: An Australian Approach -- Chapter 16. Support for Students with Special Educational Needs in Universities in Hong Kong: An Overview of the Issues -- Chapter 17. School-to-Work Transition: Support for Students with Moderate-to-Severe Special Educational Needs in Singapore -- Part 4. Useful Tools for Assessment and Intervention -- Chapter 18. Transition Assessment and Goal Generator (TAGG): Useful Tool to Assess Non-Academic Skills -- Chapter 19. Utilising Screen Reader to Support the Transitions of Learners with Visual Impairment -- Chapter 20. Life Design, Inclusion and Sustainable Development: Constructs, Dimensions and New Instruments to Stimulate a Quality Future Design for All -- Chapter 21. Assessing Career Life Skills Self-Efficacy of Students with Special Educational Needs: A Comparative Study in Hong Kong.s
Keywords: Professional education; Vocational education; Educational psychology; Education$1 (BPsychology.s; Educational sociology; Professional & Vocational Education; Educational Psychology; Sociology of Education